Awareness of coastal floods in impoverished subsiding coastal communities in Jakarta: Tsunamis, typhoon storm surges and dyke-induced tsunamis. (August 2017) - Esteban, Miguel; Takagi, Hiroshi; Mikami, Takahito; Aprilia, Aretha; Fujii, Daisuke; Kurobe, Shota; Utama, Nuki Agya
Abstract: Sea level rise will pose a significant challenge to coastal settlements throughout the planet and is likely to disproportionately affect poorer communities, which are usually located in particularly vulnerable areas. Coastal areas in Jakarta have been experiencing rapid subsidence in recent years, and could serve to illustrate the likely challenges that future sea level rise could have on such communities. To ascertain the level of awareness about the threats facing them questionnaire surveys were conducted amongst one relatively poor community that is situated below sea level, protected from the sea by a thin concrete dyke. The results show that while local inhabitants appear to be aware about the hazards they face, many seem to underestimate their severity, possibly due to a high frequency of exposure in the recent past. The situation in the area appears to be worsening with each passing year, and it is imperative that remedial actions to halt ground subsidence are carried out and/or important remedial actions to adapt to the ground subsidence are implemented. Failure to do so could eventually result in a significant loss of life in the area.